2017
DOI: 10.1161/jaha.116.005042
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐Specific Relationship Between Serum Uric Acid and Risk of Stroke: A Dose‐Response Meta‐Analysis of Prospective Studies

Abstract: BackgroundConflicting findings of the association between serum uric acid (UA) and stroke have been reported in both men and women, and it is unclear whether this association was different between men and women. We preformed this meta‐analysis to assess the sex‐specific effect of serum UA on the risk of stroke and its subtypes.Methods and ResultsProspective studies that reported sex‐specific association of UA levels with stroke or reported in a certain sex were included. Dose‐response relationships were assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
53
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 46 publications
(101 reference statements)
4
53
2
1
Order By: Relevance
“…Although Jiaqi et al failed to show that an elevated SUA level is an independent predictor for total and ischemic strokes in men, they showed a J-shaped risk trend in men, which is consistent with the results from a recent meta-analysis ( Fig. 1) [6]. Many reports about the sex and age differences in SUA have been published [12,13].…”
supporting
confidence: 72%
See 3 more Smart Citations
“…Although Jiaqi et al failed to show that an elevated SUA level is an independent predictor for total and ischemic strokes in men, they showed a J-shaped risk trend in men, which is consistent with the results from a recent meta-analysis ( Fig. 1) [6]. Many reports about the sex and age differences in SUA have been published [12,13].…”
supporting
confidence: 72%
“…Another meta-analysis study by Zhong et al showed similar results: elevated SUA levels were significantly associated with a modestly increased risk of stroke in both men (RR 1.10 per 1 mg/dL increase in SUA) and women (RR 1.11) ( Fig. 1) [6]. There seems to be no doubt about the relationship between SUA and stroke.…”
mentioning
confidence: 61%
See 2 more Smart Citations
“…The electroanalytical performance of the MN system was evaluated through examining the response to uric acid. The latter is a common biomarker in a range of clinical conditions, such as hypertension [22], kidney function [23], stroke [24] and cardiovascular disease [25,26]. It is little surprise therefore that there is an extensive literature base on its electrochemical detection and, with continuing advances in 2D carbon nanomaterials and other catalytic particles, continues to hold the interest of the diagnostics [27][28][29][30][31].…”
Section: Fabrication Methodologymentioning
confidence: 99%